The E-mail Security System Using El-Gamal Hybrid Algorithm and AES (Advanced Encryption Standard) Algorithm - Parenreng‬, Jumadi Mabe; mustari, Sahraeni Maulida; Wahid, Abdul (Internet of Things and Artificial Intelligence Journal, 2022)
E-mail is a medium of long-distance communication via the internet, which is currently often used for message exchange needs. But the use of e-mail has security problems, especially regarding data leakage when sending messages via e-mail. One of the efforts to improve the security of data and information is the application of cryptographic techniques and methods, namely end-to-end encryption. Cryptography is the science of reducing the risk of security threats by encrypting and decrypting data and information. In the implementation of the e-mail system, at least 2 (two) suitable encryption techniques are needed, namely symmetric encryption techniques to encrypt messages and data to be sent via e-mail effectively and efficiently, and asymmetric encryption techniques used to distribute keys used by symmetric encryption. Therefore, in this study, we use the El-Gamal encryption model to distribute the symmetric key, and the AES encryption model is a fairly secure algorithm to protect message data or confidential information.